2012
DOI: 10.1002/dmrr.2278
|View full text |Cite
|
Sign up to set email alerts
|

A study on the association of serum 1,5‐anhydroglucitol levels and the hyperglycaemic excursions as measured by continuous glucose monitoring system among people with type 2 diabetes in China

Abstract: BackgroundBlood glucose excursion is an important component of the glycaemic burden, but there are no indexes that can directly reflect them. The aim was to evaluate the values and significance of serum 1,5-anhydroglucitol (1,5-AG) in people with type 2 diabetes mellitus in China and to elucidate the relationship between 1,5-AG and traditional indexes of glycaemic excursions by continuous glucose monitoring.MethodsA total of 576 healthy adults and 292 patients were included, and their 1,5-AG, fasting blood glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Previous studies have shown that glycemic distributions vary among different races. For example, in the European population, diabetes patients mainly present with increased FPG 7 , 8 , whereas in the Asian population, diabetes patients exhibit postprandial hyperglycemia 18 , which was also observed in the current study. It was reported that 1,5-AG is clearly superior to HbA 1c in the accessment of postprandial glucose levels, especially for patients with HbA 1c < 8% 17 , 18 .…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown that glycemic distributions vary among different races. For example, in the European population, diabetes patients mainly present with increased FPG 7 , 8 , whereas in the Asian population, diabetes patients exhibit postprandial hyperglycemia 18 , which was also observed in the current study. It was reported that 1,5-AG is clearly superior to HbA 1c in the accessment of postprandial glucose levels, especially for patients with HbA 1c < 8% 17 , 18 .…”
Section: Discussionsupporting
confidence: 83%
“…1,5-AG in males was much higher than in females in our study, which was consistent with some other previous studies. 23,24,28,29 The positive correlation between UA and 1,5-AG found in this study may partly explain this situation as males had much higher UA than females. Previous studies 30 suggested that this may be attributed to the physical differences in the renal excretion rate between genders.…”
Section: Discussionmentioning
confidence: 53%
“…Mealtime faster aspart and IAsp were effective in controlling PPG (assessed by both the meal test and SMPG) and improved levels of 1,5-AG, a marker for postprandial hyperglycemia (22,23). In studies of basal-bolus therapy in type 2 diabetes, changes in HbA 1c are often small and nonsignificant (;0.09%) (21).…”
Section: Discussionmentioning
confidence: 99%